ANALISIS PERKEMBANGAN KEPUTUSAN PENDANAAN DAN ALOKASI DANA TERHADAP PERKEMBANGAN SISA HASIL USAHA PADA KOPDIT PINTU AIR CABANG ATAMBUA - Pasi, Patricia N N; Ndoen, Wehelmina M; Foenay, Christien C (Universitas Nusa Cendana, 2022)
This research was conducted at the Atambua branch of the Pintu Air Credit Cooperative. The purpose of this study is to analyze the development of funding decisions that only use own capital and allocation of of fundsin the form of lending to members on the development of the remaining results of the Atambua branch of the Pintu Air Credit Cooperative. The data source used is primary data and secondary data. Primary data is in the form of data obtained directly from the source at the Atambua Branch of the Pintu Air Credit Cooperative in the form of interviews with cooperative leaders and staff. Secondary data used, financial statements and statistical data. The data analysis technique used is descriptive quantitative. The results of data analysis are : (1) An increase in own capital can increase the acquisition of the remaining operating results, (2) An increase in lending to members can increase the acquisition of the remaining operating results, (3) The increase in own capital and the provision of loans simultaneously can increase the acquisition of the remaining operating income. Keywords : Funding Decisions, Budget Allocation, Remaining Results Of Operations